Exosome-mediated transfer of CD44 from high-metastatic ovarian cancer cells promotes migration and invasion of low-metastatic ovarian cancer cells - Xiameng Shen; Conghui Wang; Huihui Zhu; Yaping Wang; Xinyu Wang; Xiaodong Cheng; Wanzhong Ge; Weiguo Lu (BMC, 2021)
Abstract Objective To investigate the detailed roles and mechanisms of tumor-derived exosomes in progression and metastasis of ovarian cancer in vitro. Methods Exosomes were isolated by differential centrifugation method; the morphology, size and biological markers of exosomes were separately defined by transmission electron microscopy, nanoS90 and Western blotting; Trans-well chambers assay was used to assess the ability of migration and invasion of recipient cells uptaking the exosomes from HO8910PM cells. The downstream molecule was screened by mass spectrometry.CD44 was identified by western blotting and the function of CD44 was identified by trans-well chambers assay and CCK8 assay. Results Exosomes derived from HO8910PM cells could be transferred to HO8910 cells and promote cell migration and invasion in the recipient cells of ovarian cancer. And CD44 could be transferred to the HO8910 cells through exosomes from HO8910PM cells and influence the migration and invasion ability of HO8910 cells. Conclusion The more aggressive subpopulation can transfer a metastatic phenotype to the less one via secreting exosomes within a heterogeneous tumor. CD44 may be a potential therapeutic approach for ovarian cancer.